Social Organisation and Economic Development - Nicole W. Biggart (Journal of Economic Sociology, 2010)
Policy makers and scholars have been searching for the magic key to unlock the economic potential of underdeveloped regions. I will argue that there is no single "key", but rather that research in economic sociology shows that development depends on utilizing the historically developed patterns of social organization. Societies do best when they pursue economic activities for which their social structure gives them a comparative advantage.